Patch tests - Rosana Lazzarini; Ida Duarte; Alessandra Lindmayer Ferreira (Sociedade Brasileira de Dermatologia, 2013)
Patch tests were introduced as a diagnostic tool in the late nineteenth century. Since then, they have improved considerably becoming what they are today. Patch tests are used in the diagnostic investigation of contact dermatitis worldwide. Batteries or series previously studied and standardized should be used in patch testing. The methodology is simple, but it requires adequate training for the results to be correctly interpreted and used. Despite having been used for over a century, it needs improvement like all other diagnostic techniques in the medical field.